New species of Cercospora, Mycovellosiella and Phaeoisariopsis - and KAMAL, M. K. KHAN, R. K. VERMA (Indian Phytopathology, 2002)
Cercospora pteridigena sp. nov. on Adiantum venustum, Mycovellosiella urariae sp. nov. and Phaeoisar iop sis fabacearum sp. novo on Uraria hamosa and Phaeoisariop sis woodfordiae sp. novo on Woodfordia fructicosa are described, illustrated and compared with closely related species.